A systematic review on the accuracy of zirconia crowns and fixed dental prostheses. Issue 1 (1st January 2020) - Svanborg, Per
Abstract: Purpose: The aim of this study was to review the fit and assess the accuracy of tooth-supported single and multi-unit zirconia fixed dental prostheses. Background: The fit of zirconia restorations has been reported in several studies, but the accuracy of the manufacturing process is seldom discussed or used when drawing conclusions on the fit. Materials and methods: A literature search of articles published in PubMed between 2 March 2013 and 1 February 2018 was performed using clearly defined inclusion and exclusion criteria. 841 articles were found and 767 were excluded after screening the title and abstract. After full-text analysis another 60 articles were excluded which left 14 articles to be included for data extraction. Fit was the mean of distances reported in the studies and accuracy was the fit minus the pre-set spacer Results: For marginal gap of single crowns and multi-unit FDPs combined, the fit was 83 μm and the accuracy was 59 μm. The internal gap fit was 111 μm and the accuracy 61 μm. For the total gap, the fit was 101 μm, and the accuracy of the zirconia restorations was 53 μm. Conclusions: Within the limitations of the present systematic review the fit of zirconia single crowns and multi-unit FDPs may be regarded as clinically acceptable, and the accuracy of the manufacturing of zirconia is ∼60 μm for marginal, internal, and total gap. Also, digital impressions seem to be associated with a smaller gap value.